Induced seismicity by impoundment or hydraulic fracturing operation? A case study in the Xiannvshan Fault area of the Three Gorges Reservoir region - Tong, Guangqin; Zhu, Xiangfeng; Qin, Weibing; Zhou, Lu (Frontiers in Earth Science, 2025)
Abundant and well-documented seismic data have shown that there is a significant correlation between the earthquakes and water impoundment in the Three Gorges Reservoir Region and hydraulic fracturing operations on Well EYY1 and Well EYY2 within this area were conducted to stimulate the shale gas. Monitoring detected numerous induced microseismic events during these industrial activities. However, discriminative analysis between reservoir-induced seismicity and hydraulic fracturing induced seismicity remains conspicuously absent. This paper provides a case study in the Three Gorges Reservoir Region where water impoundment and hydraulic fracturing operation were simultaneously conducted in a certain time. Findings show that most of the micro and small earthquakes were induced by the impoundment of the Three Gorges Reservoir, and were mainly distributed along the Yangtze River and its branches during the year of 2016–2019. The emerging cluster of earthquakes in the Xiannvshan Fault area of the Three Gorges Reservoir Region was induced by hydraulic fracturing on Well EYY1 and Well EYY2, rather than by impoundment, and the relationship between seismicity observed and hydraulic fracturing activities belongs to the rapid-response type. The emerging cluster of earthquakes observed in the area are predominantly associated with rock fracturing processes controlled by pre-existing natural fractures and in-situ stress regimes, with no evidence suggesting fault reactivation induced by hydraulic fracturing operations.